INVESTMENTS ROLE IN FREE ECONOMIC ZONES - Adilova G. J; Shodiboeva D.F (Galaxy International Interdisciplinary Research Journal, 2021)
This article examines the history of the emergence of free economic zones, their role in the country's economy, the organization of sufficiently effective free economic zones and methods for accurately assessing their effectiveness, as well as the foreign practice of creating effective free economic zones. The study also emphasizes the scientific, theoretical and practical significance of this study, as well as the current state of free economic zones in Uzbekistan, the legal framework for their organization, as well as the advantages and disadvantages of these legal frameworks for participants in free economic zones. In the course of the study, the available data and analysis of studies by foreign researchers made it possible to give recommendations on the existing problems inthe activity of free economic zones in the country today and ways to increase their effectiveness. Practical proposals have also been developed to improve the financial and economic indicators of SEZ for the development of the industry.